Multi-decadal resilience (2002–2023) of subtropical coral communities in the Solitary Islands, eastern Australia, despite severe cumulative disturbances - Hamish A. Malcolm; Marine Lechene; Renata Ferrari; Curtis Champion; Steven J. Dalton; Maria Beger; James Cant; Fiona Chong; Wanchien Victoria Hsiao; Sun W. Kim; Liam Lachs; Stephen D. A. Smith; et al. (Coral Reefs, 2026)

Risky purchases – A study of consumers’ risk perceptions of plant-based leather alternatives - Darya Badiei Khorsand; Amy Benstead; Victoria Stephens; Janine Dixon; Gianpaolo Vignali; Daniella Ryding (Journal of Cleaner Production, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Optimising ecological and engineering outcomes of hybrid mangrove living shorelines using life-cycle informed restoration - Roma O. Bodycomb; Stephen E. Swearer; Andrew W.M. Pomeroy; Brendan S. Lanham; Melanie J. Bishop; Victoria J. Cole; Nicholas Colman; Marco Ghisalberti; Jack Grant; Brian Hughes; Charlotte A. Jenkins; Ryan J. Lowe; et al. (Journal of Environmental Management, 2026)

CD44 antagonism after traumatic brain injury influences the adult neurogenic niche and behavioral outcomes - Jaclyn Iannucci; Marita John; Stephen Oderinde; Gabriel Maisonnave Arisi; Victoria Arismendi; Aleksandr Pereverzev; Lee A. Shapiro (Brain Structure and Function, 2026)

Isotopic constraints on volcano-tectonically controlled assimilation at Campi Flegrei, Italy - Fay M. Amstutz; Michael J. Stock; Victoria C. Smith; Roberto Isaia; David van Acken; Stefano Vitale; Jacopo Natale; J. Stephen Daly; Adrian Boyce (Chemical Geology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Pre-surgery gut microbial diversity and abundance are associated with post-surgery onset of cachexia in colorectal cancer patients: the ColoCare Study - Mmadili N. Ilozumba; Maria F. Gomez; Tengda Lin; Caroline Himbert; June L. Round; W. Zac Stephens; Christy A. Warby; Sheetal Hardikar; Christopher I. Li; Jane C. Figueiredo; Victoria Damerell; Gary C. Fillmore; et al. (Cancer Causes & Control, 2025)
Background Cachexia accounts for about 20% of all cancer-related deaths and it is indicative of poor prognosis and progressive functional impairment. The role of the gut microbiome in the development of cachexia in colorectal cancer (CRC) patients has not been established. Methods Pre-surgical stool samples from n = 103 stage I–III CRC patients in the ColoCare Study were analyzed using 16S rRNA gene sequencing (Illumina) to characterize fecal bacteria. We calculated estimates of alpha- and beta-diversity and a priori- and exploratory-selected bacterial relative abundance. Using Fearon criteria, cachexia onset at 6 months post-surgery was defined as > 5% weight loss over the past 6 months and/or body mass index (BMI) of < 20 kg/m 2 and weight loss of > 2%. Associations of microbial metrics with cachexia onset were estimated using multivariable logistic regression models. Results Higher alpha-diversity was positively associated with cachexia onset, with stronger associations in females, patients < 65 years, those receiving adjuvant treatment, consuming high fiber, or with energy intake outside USDA recommendations ( p < 0.05). Porphyromonas (OR = 0.51, 95% CI 0.26–0.89, p = 0.03) and Actinomyces (OR = 0.72, 95% CI 0.48–1.03, p = 0.08) were inversely associated with cachexia, although the association for Actinomyces did not reach statistical significance. Stratified analyses revealed a stronger inverse association between Porphyromonas and cachexia onset in males, patients with rectal or stage III tumors, those receiving neoadjuvant treatment, physically inactive individuals, and those consuming low fiber. However, these associations did not reach statistical significance (0.05 ≤ p < 0.10). Conclusion Higher gut microbial alpha-diversity and lower relative abundances of the genera Porphyromonas and Actinomyces in pre-surgery stool samples were associated with onset of cachexia in CRC patients six months post-surgery. This is the first study to explore a link between the gut microbiome and cachexia in CRC patients, providing novel insights into the biology of cachexia and potential clinical interventions.

Genomic insights and immunoinformatics-driven design of a multi-epitope subunit vaccine candidate against Shamonda virus - Elijah Kolawole Oladipo; Stephen Feranmi Adeyemo; James Akinwumi Ogunniran; Better Olaronke Ajiboye; Victoria Ajike Alabi; Dorcas Ifeoluwa Odemakinde; Hope Judah Ogunmodede; Zainab Oluwaranti Hammed; Mercy Adesewa Adebanjo; Simbiat Motunrayo Arowolo; Naimot Ogunwale; Flourish Boluwatife Remi-Aworemi; et al. (In Silico Pharmacology, 2025)

Grounding the conversation on loss and damage: insights from sense-making analysis with Pacific leaders - Stephen Woroniecki; Pamela Feetham; Björn-Ola Linnér; Api Movono; Priyatma Singh; Franco Vaccarino; Victoria Wibeck; Kristin Zeiler (Climatic Change, 2025)
The concept of Loss and Damage (L&D) is gaining increased attention within and outside of international climate negotiations, and by a broader array of actors looking to address the personal, practical, and political changes wrought by the impacts of climate change. While the original use of the term has developed within the international negotiations, the concept is increasingly tasked with making sense of, and dealing with, the impacts of climate change at national and local levels. In this context, there is a need to understand how the concept of L&D relates to people’s experiences of and potential responses to the impacts of climate change. We address this gap by drawing on dialogical sense-making analysis, that highlights how language both shapes, and is shaped by, the social interactions in which it is used. Our in-depth qualitative analysis builds on ten conversations with Pacific leaders familiar with Loss and Damage in international discussions as well as national and local-level experiences of actually-occurring losses and damages. We show how the depth and range of experiences that people articulate are often at odds with the meanings associated with the concept of Loss and Damage, which are primarily orientated towards the international climate negotiations. We therefore question whether and how the concept is relevant to these experiences and forms of sense-making. Grounding the concept of L&D will require attention to the kinds of conversations it is enabling, and how they can become more inclusive of plural perspectives, needs, knowledges and values.

Post-occupancy evaluation of public and private building architectural design performance in the tropical rainforest climate of Owerri, Southern Nigeria - Stephen Ikpendu Nwankwo; Chidiuto Victoria Nwankwo (Theoretical and Applied Climatology, 2025)

Incorporating buccal mass planar mechanics and anatomical features improves neuromechanical modeling of Aplysia feeding behavior - Michael J. Bennington; Ashlee S. Liao; Ravesh Sukhnandan; Bidisha Kundu; Stephen M. Rogers; Jeffrey P. Gill; Jeffrey M. McManus; Gregory P. Sutton; Hillel J. Chiel; Victoria A. Webster-Wood (Biological Cybernetics, 2025)
To understand how behaviors arise in animals, it is necessary to investigate both the neural circuits and the biomechanics of the periphery. A tractable model system for studying multifunctional control is the feeding apparatus of the marine mollusk Aplysia californica . Previous in silico and in roboto models have investigated how the nervous and muscular systems interact in this system. However, these models are still limited in their ability to match in vivo data both qualitatively and quantitatively. We introduce a new neuromechanical model of Aplysia feeding that combines a modified version of a previously developed neural model with a novel biomechanical model that better reflects the anatomy and kinematics of Aplysia feeding. The model was calibrated using a combination of previously measured biomechanical parameters and hand-tuning to behavioral data. Using this model, simulated feeding experiments were conducted, and the resulting behavioral metrics were compared to animal data. The model successfully produces three key behaviors seen in Aplysia and demonstrates a good quantitative agreement with biting and swallowing behaviors. Additional work is needed to match rejection behavior quantitatively and to reflect qualitative observations related to the relative contributions of two key muscles, the hinge and I3. Future improvements will focus on incorporating the effects of deformable 3D structures in the simulated buccal mass.

Assessing changes between two years in macrobenthic invertebrate communities in four sub-tropical Australian estuaries - Muhammad M. Islami; Adam Davey; Stephen D.A. Smith; Victoria J. Cole; Rachel Przeslawski; Kirsten Benkendorff (Regional Studies in Marine Science, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Continental-scale sediment mixing and dispersal across northern Gondwana: detrital zircon U-Pb-O-Hf isotopic evidence from the Cambro-Ordovician sandstones overlying the Arabian Shield - Fitsum Girum Yeshanew; Martin J. Whitehouse; Victoria Pease; Eszter Badenszki; J. Stephen Daly (International Geology Review, 2025)

Effects of bioprocessing on elemental composition, physicochemical, techno-functional, storage and sensorial properties of gluten-free flour from fonio and date fruit - Oluwatobi Victoria Obayomi; Abiola Folakemi Olaniran; Stephen Olugbemiga Owa (Food Bioscience, 2024)

Mutagenesis on a complex mouse genetic background by site-specific nucleases - Benjamin Davies; Lucy Trelfa; Victoria S. Rashbrook; Edward Drydale; Rachel Martin; Boyan Bai; Jedrzej Golebka; Daniel Stephen Biggs; Keith M. Channon; Shoumo Bhattacharya; Gillian Douglas (Transgenic Research, 2024)
Mouse models with complex genetic backgrounds are increasingly used in preclinical research to accurately model human disease and to enable temporal and cell-specific evaluation of genetic manipulations. Backcrossing mice onto these complex genetic backgrounds takes time and leads to significant wastage of animals. In this study, we aimed to evaluate whether site-specific nucleases could be used to generate additional genetic mutations in a complex genetic background, using the REVERSA mouse model of atherosclerosis, a model harbouring four genetically altered alleles. The model is comprised of a functional null mutation in the Ldlr gene in combination with a ApoB100 allele, which, after high-fat diet, leads to the rapid development of atherosclerosis. The regression of the pathology is achieved by inducible knock-out of the Mttp gene. Here we report an investigation to establish if microinjection of site-specific nucleases directly into zygotes prepared from the REVERSA could be used to investigate the role of the ATP binding cassette transporter G1 (ABCG1) in atherosclerosis regression. We show that using this approach we could successfully generate two independent knockout lines on the REVERSA background, both of which exhibited the expected phenotype of a significant reduction in cholesterol efflux to HDL in bone marrow-derived macrophages. However, loss of Abcg1 did not impact atherosclerosis regression in either the aortic root or in aortic arch, demonstrating no important role for this transporter subtype. We have demonstrated that site-specific nucleases can be used to create genetic modifications directly onto complex disease backgrounds and can be used to explore gene function without the need for laborious backcrossing of independent strains, conveying a significant 3Rs advantage.

The lived experiences of transformations: The role of sense-making and phenomenology analyses - Stephen Woroniecki; Victoria Wibeck; Kristin Zeiler; Björn-Ola Linnér (Environmental Science & Policy, 2024)

Addressing Barriers and Facilitators to African Americans’ and Hispanics’ Participation in Clinical and Genomic Research Through a Bioethical Sensitive Video - Victoria Churchill; Yu-Mei Schoenberger; Vivian L. Carter; Jamirah Y. Chevrin; Windy Dean-Colomb; Roland Matthews; Desiree Rivers; Stephen O. Sodeke; Jonathan Ezer; Brian M. Rivers (Journal of Cancer Education, 2024)
Research advances on effective methods to prevent, diagnose, and treat cancer continue to emerge through clinical and genomic research. Most clinical trial and genomic research participants identify as White which limits the generalizability of research findings to non-White populations. With the development and access to technology, digital delivery of salient and tailored health education may provide innovative pathways to increase representation of African Americans (AA) and Hispanics in research. This project focused on the creation of a bioethical sensitive education video aimed at increasing participation in clinical trials and genomic research by bringing together experts from the community, healthcare, biomedical research, and public health. The goal was to utilize existing educational resources to create a tailored message to address AA/Hispanics’ beliefs, values, and bioethical concerns related to participation in clinical and genomic research. Models of behavior change and communication theories were leveraged to frame key components of the message, which then informed the framework for the animated video. Development of the video consisted of six iterative phases: 1) writing sessions; 2) storyboarding; 3) animating; 4) screening/revisions; 5) acceptability testing; 6) finalization. The final animated video is approximately 5 min in length and covers several topics including the goal of clinical research, disparities in research participation, bioethical concerns, and genomic research regulations. Increasing AA and Hispanic participation in clinical and genomic research is imperative to achieving health equity. Tailored messages via short videos may assist in addressing the barriers and facilitators towards research participation and increase intentions to enroll in trials.

mRNA vaccine design for Epstein–Barr virus: an immunoinformatic approach - Elijah Kolawole Oladipo; Temitope Michael Akinleye; Stephen Feranmi Adeyemo; Modinat Wuraola Akinboade; Kehinde Favour Siyanbola; Victoria Ademide Adetunji; Olukayode Abimbola Arowosegbe; Victoria Kehinde Olatunji; Esther Oluwadarasimi Adaramola; Hezekiah Omotayo Afolabi; Christianah Damilola Ajani; Taiwo Pleasure Siyanbola; et al. (In Silico Pharmacology, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Towards richer knowledge partnerships between ecology and ethnoecology - Zsolt Molnár; Yildiz Aumeeruddy-Thomas; Dániel Babai; Sandra Díaz; Stephen T. Garnett; Rosemary Hill; Peter Bates; Eduardo S. Brondízio; Joji Cariño; László Demeter; Álvaro Fernández-Llamazares; Maximilien Guèze; et al. (Trends in Ecology & Evolution, 2024)

Long-term effects of THC exposure on reward learning and motivated behavior in adolescent and adult male rats - Briac Halbout; Collin Hutson; Leann Hua; Victoria Inshishian; Stephen V. Mahler; Sean B. Ostlund (Psychopharmacology, 2023)
Rationale The endocannabinoid system makes critical contributions to reward processing, motivation, and behavioral control. Repeated exposure to THC or other cannabinoid drugs can cause persistent adaptions in the endocannabinoid system and associated neural circuitry. It remains unclear how such treatments affect the way rewards are processed and pursued. Objective and methods We examined if repeated THC exposure (5 mg/kg/day for 14 days) during adolescence or adulthood led to long-term changes in rats’ capacity to flexibly encode and use action-outcome associations for goal-directed decision making. Effects on hedonic feeding and progressive ratio responding were also assessed. Results THC exposure had no effect on rats’ ability to flexibly select actions following reward devaluation. However, instrumental contingency degradation learning, which involves avoiding an action that is unnecessary for reward delivery, was augmented in rats with a history of adult but not adolescent THC exposure. THC-exposed rats also displayed more vigorous instrumental behavior in this study, suggesting a motivational enhancement. A separate experiment found that while THC exposure had no effect on hedonic feeding behavior, it increased rats’ willingness to work for food on a progressive ratio schedule, an effect that was more pronounced when THC was administered to adults. Adolescent and adult THC exposure had opposing effects on the CB1 receptor dependence of progressive ratio performance, decreasing and increasing sensitivity to rimonabant-induced behavioral suppression, respectively. Conclusions Our findings reveal that exposure to a translationally relevant THC exposure regimen induces long-lasting, age-dependent alterations in cognitive and motivational processes that regulate the pursuit of rewards.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Wilderness forms and their implications for global environmental policy and conservation - Katharina‐Victoria Pérez‐Hämmerle; Katie Moon; Rubén Venegas‐Li; Sean Maxwell; Jeremy S. Simmonds; Oscar Venter; Stephen T. Garnett; Hugh P. Possingham; James E. M. Watson (Conservation Biology, 2022)
With the intention of securing industry‐free land and seascapes, protecting wilderness entered international policy as a formal target for the first time in the zero draft of the Post‐2020 Global Biodiversity Framework under the Convention on Biological Diversity. Given this increased prominence in international policy, it is timely to consider the extent to which the construct of wilderness supports global conservation objectives. We evaluated the construct by overlaying recently updated cumulative human pressure maps that offer a global‐scale delineation of industry‐free land as wilderness with maps of carbon stock, species richness, and ground travel time from urban centers. Wilderness areas took variable forms in relation to carbon stock, species richness, and proximity to urban centers, where 10% of wilderness areas represented high carbon and species richness, 20% low carbon and species richness, and 3% high levels of remoteness (>48 h), carbon, and species richness. Approximately 35% of all remaining wilderness in 2013 was accessible in

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Altered structure of bat–prey interaction networks in logged tropical forests revealed by metabarcoding - David R. Hemprich‐Bennett; Victoria A. Kemp; Joshua Blackman; Matthew J. Struebig; Owen T. Lewis; Stephen J. Rossiter; Elizabeth L. Clare (Molecular Ecology, 2021)
Habitat degradation is pervasive across the tropics and is particularly acute in Southeast Asia, with major implications for biodiversity. Much research has addressed the impact of degradation on species diversity; however, little is known about how ecological interactions are altered, including those that constitute important ecosystem functions such as consumption of herbivores. To examine how rainforest degradation alters trophic interaction networks, we applied DNA metabarcoding to construct interaction networks linking forest‐dwelling insectivorous bat species and their prey, comparing old‐growth forest and forest degraded by logging in Sabah, Borneo. Individual bats in logged rainforest consumed a lower richness of prey than those in old‐growth forest. As a result, interaction networks in logged forests had a less nested structure. These network structures were associated with reduced network redundancy and thus increased vulnerability to perturbations in logged forests. Our results show how ecological interactions change between old‐growth and logged forests, with potentially negative implications for ecosystem function and network stability.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

A Co-Crystallised Cobalt(II) Cluster of Pyridinedicarboxylic Acid (PDC) as a Luminescent Material for Selective Sensing of Methanol - Victoria T. Olayemi; Adedibu C. Tella; Folahan A. Adekola; Hadley S. Clayton; Adetola C. Oladipo; Gift Mehlana; Adeniyi S. Ogunlaja; Oluwatobi S. Oluwafemi; Joseph O. Ogar; Stephen P. Argent; Robert Mokaya (Journal of Fluorescence, 2021)

Long-Term Impacts of Invasive Insects and Pathogens on Composition, Biomass, and Diversity of Forests in Virginia’s Blue Ridge Mountains - Kristina J. Anderson-Teixeira; Valentine Herrmann; Wendy B. Cass; Alan B. Williams; Stephen J. Paull; Erika B. Gonzalez-Akre; Ryan Helcoski; Alan J. Tepley; Norman A. Bourg; Christopher T. Cosma; Abigail E. Ferson; Caroline Kittle; et al. (Ecosystems, 2021)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Anatomical and Behavioral Assessment of Larval Zebrafish (Danio rerio) Reared in Anacostia River Water Samples - Rebecca L. Wilken; Aikerim Imanalieva; Stephen MacAvoy; Victoria P. Connaughton (Archives of Environmental Contamination and Toxicology, 2020)

Integrating an individual-based model with approximate Bayesian computation to predict the invasion of a freshwater fish provides insights into dispersal and range expansion dynamics - Victoria Dominguez Almela; Stephen C. F. Palmer; Phillipa K. Gillingham; Justin M. J. Travis; J. Robert Britton (Biological Invasions, 2020)
Short-distance dispersal enables introduced alien species to colonise and invade local habitats following their initial introduction, but is often poorly understood for many freshwater taxa. Knowledge gaps in range expansion of alien species can be overcome using predictive approaches such as individual based models (IBMs), especially if predictions can be improved through fitting to empirical data, but this can be challenging for models having multiple parameters. We therefore estimated the parameters of a model implemented in the RangeShifter IBM platform by approximate Bayesian computation (ABC) in order to predict the further invasion of a lowland river (Great Ouse, England) by a small-bodied invasive fish (bitterling Rhodeus sericeus ). Prior estimates for parameters were obtained from the literature and expert opinion. Model fitting was conducted using a time-series (1983 to 2018) of sampling data at fixed locations and revealed that for 5 of 11 model parameters, the posterior distributions differed markedly from prior assumptions. In particular, sub-adult maximum emigration probability was substantially higher in the posteriors than priors. Simulations of bitterling range expansion predicted that following detection in 1984, their early expansion involved a relatively high population growth rate that stabilised after 5 years. The pattern of bitterling patch occupancy was sigmoidal, with 20% of the catchment occupied after 20 years, increasing to 80% after 30 years. Predictions were then for 95% occupancy after 69 years. The development of this IBM thus successfully simulated the range expansion dynamics of this small-bodied invasive fish, with ABC improving the simulation precision. This combined methodology also highlighted that sub-adult dispersal was more likely to contribute to the rapid colonisation rate than expert opinion suggested. These results emphasise the importance of time-series data for refining IBM parameters generally and increasing our understanding of dispersal behaviour and range expansion dynamics specifically.

Alcohol intake, tobacco smoking, and esophageal adenocarcinoma survival: a molecular pathology epidemiology cohort study - R. Stephen McCain; Damian T. McManus; Stephen McQuaid; Jacqueline A. James; Manuel Salto-Tellez; Nathan B. Reid; Stephanie Craig; Chintapuza Chisambo; Victoria Bingham; Eamon McCarron; Eileen Parkes; Richard C. Turkington; et al. (Cancer Causes & Control, 2020)
Purpose To investigate the association between cigarette smoking, alcohol consumption, and esophageal adenocarcinoma survival, including stratified analysis by selected prognostic biomarkers. Methods A population-representative sample of 130 esophageal adenocarcinoma patients (n = 130) treated at the Northern Ireland Cancer Centre between 2004 and 2012. Cox proportional hazards models were applied to evaluate associations between smoking status, alcohol intake, and survival. Secondary analyses investigated these associations across categories of p53, HER2, CD8, and GLUT-1 biomarker expression. Results In esophageal adenocarcinoma patients, there was a significantly increased risk of cancer-specific mortality in ever, compared to never, alcohol drinkers in unadjusted (HR 1.96 95% CI 1.13–3.38) but not adjusted (HR 1.70 95% CI 0.95–3.04) analysis. This increased risk of death observed for alcohol consumers was more evident in patients with normal p53 expression, GLUT-1 positive or CD-8 positive tumors. There were no significant associations between survival and smoking status in esophageal adenocarcinoma patients. Conclusions In esophageal adenocarcinoma patients, cigarette smoking or alcohol consumption was not associated with a significant difference in survival in comparison with never smokers and never drinkers in fully adjusted analysis. However, in some biomarker-selected subgroups, ever-alcohol consumption was associated with a worsened survival in comparison with never drinkers. Larger studies are needed to investigate these findings, as these lifestyle habits may not only be linked to cancer risk but also cancer survival.

Range-wide phylogeography of Blanding’s Turtle [Emys (= Emydoidea) blandingii] - Mark A. Jordan; Victoria Mumaw; Natalie Millspaw; Stephen W. Mockford; Fredric J. Janzen (Conservation Genetics, 2019)

Seasonal and Long-Term Dynamics in Stream Water Sodium Chloride Concentrations and the Effectiveness of Road Salt Best Management Practices - Victoria R. Kelly; Stuart E. Findlay; Stephen K. Hamilton; Gary M. Lovett; Kathleen C. Weathers (Water, Air, & Soil Pollution, 2019)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Dose effects of New Zealand blackcurrant on substrate oxidation and physiological responses during prolonged cycling - Matthew David Cook; Stephen David Myers; Mandy Lucinda Gault; Victoria Charlotte Edwards; Mark Elisabeth Theodorus Willems (European Journal of Applied Physiology, 2017)

Cardiovascular function during supine rest in endurance-trained males with New Zealand blackcurrant: a dose–response study - Matthew David Cook; Stephen David Myers; Mandy Lucinda Gault; Victoria Charlotte Edwards; Mark Elisabeth Theodorus Willems (European Journal of Applied Physiology, 2017)

Discordant CSF/plasma HIV-1 RNA in patients with unexplained low-level viraemia - Sam Nightingale; Anna Maria Geretti; Apostolos Beloukas; Martin Fisher; Alan Winston; Laura Else; Mark Nelson; Stephen Taylor; Andrew Ustianowski; Jonathan Ainsworth; Richard Gilson; Lewis Haddow; et al. (Journal of NeuroVirology, 2016)

Effects of multiple climate change stressors: ocean acidification interacts with warming, hyposalinity, and low food supply on the larvae of the brooding flat oyster Ostrea angasi - Victoria J. Cole; Laura M. Parker; Stephen J. O’Connor; Wayne A. O’Connor; Elliot Scanes; Maria Byrne; Pauline M. Ross (Marine Biology, 2016)

Rising temperatures and changing rainfall patterns in South Africa's national parks - Nicola J. van Wilgen; Victoria Goodall; Stephen Holness; Steven L. Chown; Melodie A. McGeoch (International Journal of Climatology, 2016)
Air temperatures have increased globally over the past decades, while rainfall changes have been more variable, but are taking place. In South Africa, substantial climate‐related impacts are predicted, and protected area management agencies will need to respond actively to impacts. It is critical for management agencies to understand the way in which climate is changing locally to predict impacts and respond appropriately. Here, for the first time, we quantify observable changes in temperature and rainfall in South African national parks over the past five to ten decades. Our results show significant increases in temperatures in most parks, with increases being most rapid in the arid regions of the country. Increases in the frequency of extreme high temperature events were also most pronounced in these regions. These results are consistent with other climate studies conducted in these areas. Similar increases were identified for both minimum and maximum temperatures, though absolute minimum temperatures increased at greater rates than absolute maxima. Overall, rainfall trends were less obvious, but a decrease in rainfall was observed for the southern Cape (in three parks), and an increase was detected in one park. The observed temperature changes over the last 20–50 years have in several instances already reached those predicted for near future scenarios (2035), indicating that change scenarios are conservative. These results provide individual parks with evidence‐based direction for managing impacts under current and projected changes in local climate. They also provide the management agency with sub‐regional information to tailor policy and impact monitoring. Importantly, our results highlight the critical role that individual weather stations play in informing local land management and the concerns for parks that have no local information on changes in climate.

Large genomic rearrangements in the familial breast and ovarian cancer gene BRCA1 are associated with an increased frequency of high risk features - Paul A. James; Sarah Sawyer; Samantha Boyle; Mary-Anne Young; Serguei Kovalenko; Rebecca Doherty; Joanne McKinley; Kathryn Alsop; Victoria Beshay; Marion Harris; Stephen Fox; Geoffrey J. Lindeman; et al. (Familial Cancer, 2015)

Fish community structure as an indicator of the long-term effects of the damming of an Amazonian river - Júlio C. Sá-Oliveira; Victoria J. Isaac; Stephen F. Ferrari (Environmental Biology of Fishes, 2015)

Between-subject variability: should high be the new normal? - Hesham S. Al-Sallami; Song Lim Cheah; Shiou Yii Han; Joel Liew; Jin Lim; Mary Anne Ng; Hayneil Solanki; Run Jie Soo; Victoria Tan; Stephen B. Duffull (European Journal of Clinical Pharmacology, 2014)

Microscale sulfur cycling in the phototrophic pink berry consortia of the S ippewissett S alt M arsh - Elizabeth G. Wilbanks; Ulrike Jaekel; Verena Salman; Parris T. Humphrey; Jonathan A. Eisen; Marc T. Facciotti; Daniel H. Buckley; Stephen H. Zinder; Gregory K. Druschel; David A. Fike; Victoria J. Orphan (Environmental Microbiology, 2014)
Summary Microbial metabolism is the engine that drives global biogeochemical cycles, yet many key transformations are carried out by microbial consortia over short spatiotemporal scales that elude detection by traditional analytical approaches. We investigate syntrophic sulfur cycling in the ‘pink berry’ consortia of the S ippewissett S alt M arsh through an integrative study at the microbial scale. The pink berries are macroscopic, photosynthetic microbial aggregates composed primarily of two closely associated species: sulfide‐oxidizing purple sulfur bacteria ( PB ‐ PSB 1) and sulfate‐reducing bacteria ( PB ‐ SRB 1). Using metagenomic sequencing and 34 S ‐enriched sulfate stable isotope probing coupled with nanoSIMS , we demonstrate interspecies transfer of reduced sulfur metabolites from PB ‐ SRB 1 to PB ‐ PSB 1. The pink berries catalyse net sulfide oxidation and maintain internal sulfide concentrations of 0–500 μ m . Sulfide within the berries, captured on silver wires and analysed using secondary ion mass spectrometer, increased in abundance towards the berry interior, while δ 34 S‐ sulfide decreased from 6‰ to −31‰ from the exterior to interior of the berry. These values correspond to sulfate–sulfide isotopic fractionations (15–53‰) consistent with either sulfate reduction or a mixture of reductive and oxidative metabolisms. Together this combined metagenomic and high‐resolution isotopic analysis demonstrates active sulfur cycling at the microscale within well‐structured macroscopic consortia consisting of sulfide‐oxidizing anoxygenic phototrophs and sulfate‐reducing bacteria.

Consistent proportional macronutrient intake selected by adult domestic cats (Felis catus) despite variations in macronutrient and moisture content of foods offered - Adrian K. Hewson-Hughes; Victoria L. Hewson-Hughes; Alison Colyer; Andrew T. Miller; Simon R. Hall; David Raubenheimer; Stephen J. Simpson (Journal of Comparative Physiology B, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Effect of low-dose acute tryptophan depletion on the specificity of autobiographical memory in healthy subjects with a family history of depression - Hamid A. Alhaj; Matthew Selman; Victoria Jervis; Jacqui Rodgers; Stephen Barton; R. Hamish McAllister-Williams (Psychopharmacology, 2012)

Familial renal cancer as an indicator of hereditary leiomyomatosis and renal cell cancer syndrome - Victoria M. Raymond; Casey M. Herron; Thomas J. Giordano; Stephen B. Gruber (Familial Cancer, 2012)

Erratum to: Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2011)

Hereditary prostate cancer as a feature of Lynch Syndrome - Christina M. Bauer; Anna M. Ray; Bronwen A. Halstead-Nussloch; Robert G. Dekker; Victoria M. Raymond; Stephen B. Gruber; Kathleen A. Cooney (Familial Cancer, 2011)

FAP, gastric cancer, and genetic counseling featuring children and young adults: a family study and review - Henry T. Lynch; Carrie Snyder; Janine M. Davies; Stephen Lanspa; Jane Lynch; Zoran Gatalica; Victoria Graeve; Jason Foster (Familial Cancer, 2010)

Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Comparison of defined culture systems for feeder cell free propagation of human embryonic stem cells - Veronika Akopian; Peter W. Andrews; Stephen Beil; Nissim Benvenisty; Jennifer Brehm; Megan Christie; Angela Ford; Victoria Fox; Paul J. Gokhale; Lyn Healy; Frida Holm; Outi Hovatta; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Synoptic Controls on Boundary-Layer Characteristics - Victoria A. Sinclair; Stephen E. Belcher; Suzanne L. Gray (Boundary-Layer Meteorology, 2010)

Body size‐dependent responses of a marine fish assemblage to climate change and fishing over a century‐long scale - MARTIN J. GENNER; DAVID W. SIMS; ALAN J. SOUTHWARD; GEORGINA C. BUDD; PATRICIA MASTERSON; MATTHEW MCHUGH; PETER RENDLE; EMILY J. SOUTHALL; VICTORIA J. WEARMOUTH; STEPHEN J. HAWKINS (Global Change Biology, 2010)
Commercial fishing and climate change have influenced the composition of marine fish assemblages worldwide, but we require a better understanding of their relative influence on long‐term changes in species abundance and body‐size distributions. In this study, we investigated long‐term (1911–2007) variability within a demersal fish assemblage in the western English Channel. The region has been subject to commercial fisheries throughout most of the past century, and has undergone interannual changes in sea temperature of over 2.0 °C. We focussed on a core 30 species that comprised 99% of total individuals sampled in the assemblage. Analyses showed that temporal trends in the abundance of smaller multispecies size classes followed thermal regime changes, but that there were persistent declines in abundance of larger size classes. Consistent with these results, larger‐growing individual species had the greatest declines in body size, and the most constant declines in abundance, while abundance changes of smaller‐growing species were more closely linked to preceding sea temperatures. Together these analyses are suggestive of dichotomous size‐dependent responses of species to long‐term climate change and commercial fishing over a century scale. Small species had rapid responses to the prevailing thermal environment, suggesting their life history traits predisposed populations to respond quickly to changing climates. Larger species declined in abundance and size, reflecting expectations from sustained size‐selective overharvesting. These results demonstrate the importance of considering species traits when developing indicators of human and climatic impacts on marine fauna.

Associations between endogenous sex hormone levels and mammographic and bone densities in premenopausal women - Mellissa Yong; Charlotte Atkinson; Katherine M. Newton; Erin J. Aiello Bowles; Frank Z. Stanczyk; Kim C. Westerlind; Victoria L. Holt; Stephen M. Schwartz; Wendy M. Leisenring; Johanna W. Lampe (Cancer Causes & Control, 2009)

Quantifying the impact of current and future tropospheric ozone on tree biomass, growth, physiology and biochemistry: a quantitative meta‐analysis - VICTORIA E. WITTIG; ELIZABETH A. AINSWORTH; SHAWNA L. NAIDU; DAVID F. KARNOSKY; STEPHEN P. LONG (Global Change Biology, 2009)
The northern hemisphere temperate and boreal forests currently provide an important carbon sink; however, current tropospheric ozone concentrations ([O 3 ]) and [O 3 ] projected for later this century are damaging to trees and have the potential to reduce the carbon sink strength of these forests. This meta‐analysis estimated the magnitude of the impacts of current [O 3 ] and future [O 3 ] on the biomass, growth, physiology and biochemistry of trees representative of northern hemisphere forests. Current ambient [O 3 ] (40 ppb on average) significantly reduced the total biomass of trees by 7% compared with trees grown in charcoal‐filtered (CF) controls, which approximate preindustrial [O 3 ]. Above‐ and belowground productivity were equally affected by ambient [O 3 ] in these studies. Elevated [O 3 ] of 64 ppb reduced total biomass by 11% compared with trees grown at ambient [O 3 ] while elevated [O 3 ] of 97 ppb reduced total biomass of trees by 17% compared with CF controls. The root‐to‐shoot ratio was significantly reduced by elevated [O 3 ] indicating greater sensitivity of root biomass to [O 3 ]. At elevated [O 3 ], trees had significant reductions in leaf area, Rubisco content and chlorophyll content which may underlie significant reductions in photosynthetic capacity. Trees also had lower transpiration rates, and were shorter in height and had reduced diameter when grown at elevated [O 3 ]. Further, at elevated [O 3 ], gymnosperms were significantly less sensitive than angiosperms. There were too few observations of the interaction of [O 3 ] with elevated [CO 2 ] and drought to conclusively project how these climate change factors will alter tree responses to [O 3 ]. Taken together, these results demonstrate that the carbon‐sink strength of northern hemisphere forests is likely reduced by current [O 3 ] and will be further reduced in future if [O 3 ] rises. This implies that a key carbon sink currently offsetting a significant portion of global fossil fuel CO 2 emissions could be diminished or lost in the future.

Sediment Organic Carbon in Todos Santos Bay, Baja California, Mexico - Stephen V. Smith; Silvia E. Ibarra-Obando; Victoria Díaz-Castañeda; Francisco Javier Aranda-Manteca; José D. Carriquiry; Brian N. Popp; Oscar Gonzalez-Yajimovich (Estuaries and Coasts, 2008)

Geographical distribution and disease associations of the CD45 exon 6 138G variant - Victoria Ward; Branwen J. Hennig; Kouzo Hirai; Hideki Tahara; Akihiro Tamori; Ritu Dawes; Mineki Saito; Charles Bangham; Henry Stephens; Anne E. Goldfeld; Warunee Kunachiwa; Nipapan Leetrakool; et al. (Immunogenetics, 2006)

Gross primary production is stimulated for three Populus species grown under free‐air CO 2 enrichment from planting through canopy closure - Victoria E. Wittig; Carl J. Bernacchi; Xin‐Guang Zhu; Carlo Calfapietra; Reinhart Ceulemans; Paolo Deangelis; Birgit Gielen; Franco Miglietta; Patrick B. Morgan; Stephen P. Long (Global Change Biology, 2005)
How forests will respond to rising [CO 2 ] in the long term is uncertain, most studies having involved juvenile trees in chambers prior to canopy closure. Poplar free‐air CO 2 enrichment (Viterbo, Italy) is one of the first experiments to grow a forest from planting through canopy closure to coppice, entirely under open‐air conditions using free‐air CO 2 enrichment technology. Three Populus species: P . alba , P . nigra and P . x euramericana , were grown in three blocks, each containing one control and one treatment plot in which CO 2 was elevated to the expected 2050 concentration of 550 ppm. The objective of this study was to estimate gross primary production (GPP) from recorded leaf photosynthetic properties, leaf area index (LAI) and meteorological conditions over the complete 3‐year rotation cycle. From the meteorological conditions recorded at 30 min intervals and biweekly measurements of LAI, the microclimate of leaves within the plots was estimated with a radiation transfer and energy balance model. This information was in turn used as input into a canopy microclimate model to determine light and temperature of different leaf classes at 30 min intervals which in turn was used with the steady‐state biochemical model of leaf photosynthesis to compute CO 2 uptake by the different leaf classes. The parameters of these models were derived from measurements made at regular intervals throughout the coppice cycle. The photosynthetic rates for different leaf classes were summed to obtain canopy photosynthesis, i.e. GPP. The model was run for each species in each plot, so that differences in GPP between species and treatments could be tested statistically. Significant stimulation of GPP driven by elevated [CO 2 ] occurred in all 3 years, and was greatest in the first year (223–251%), but markedly lower in the second (19–24%) and third years (5–19%). Increase in GPP in elevated relative to control plots was highest for P. nigra in 1999 and for P. x euramericana in 2000 and 2001, although in 1999 P. alba had a higher GPP than P. x euramericana . Our analysis attributed the decline in stimulation to canopy closure and not photosynthetic acclimation. Over the 3‐year rotation cycle from planting to harvest, the cumulative GPP was 4500, 4960 and 4010 g C m −2 for P. alba , P. nigra and P. x euramericana , respectively, in current [CO 2 ] and 5260, 5800 and 5000 g C m −2 in the elevated [CO 2 ] treatments. The relative changes were consistent with independent measurements of net primary production, determined independently from biomass increments and turnover.

A Regional Survey of the Microbiological Water Quality along the Shoreline of the Southern California Bight - Rachel T. Noble; John H. Dorsey; Molly Leecaster; Victoria Orozco-Borbón; Daniel Reid; Kenneth Schiff; Stephen B. Weisberg (Environmental Monitoring and Assessment, 2000)

A science-based strategy for ecological restoration in South Florida - Mark A. Harwell; John H. Gentile; Ann Bartuska; Christine C. Harwell; Victoria Myers; Jayantha Obeysekera; John C. Ogden; Stephen C. Tosini (Urban Ecosystems, 1999)